That which will truly overtake you: Qur'ān, death, and dying - Fahm, AbdulGafar Olawale (Ilorin journal of religious studies, 2021)
Death, for some people, is a topic that should be avoided. They see death as a negative and fearful event. That would seem to explain why there are various superstitious beliefs around death world over. The purpose of this study is to seek a basic understanding of the Islamic position and attitude towards death by examining the primary source of Islamic teaching - the Qur'ān. The method adopted is exegetical, drawing data primarily from the Qur'ān on the subject of death. This leads to an understanding of the various intents and meanings of the notion of death in the Qur'ān. The paper concludes that the concept of death in the Qur'ān demonstrates a consistent outlook of positivity, hence its constant exhortation to Muslims to recognize the importance of courage, self-sacrifice, truth, reality, regret, good deeds, and Allah's might on life and power.